Endo-Hepatology: The Buzz Goes Much beyond Liver Biopsy—A Narrative Review - Rajesh Puri; Zubin Sharma; Swapnil Dhampalwar; Abhishek Kathuria; Bimal Sahu (Journal of Digestive Endoscopy, 2023)
The word endo-hepatology evokes many perceptions. Some believe it to be the emerging new interventional branch and some believe it to be an extension of endoscopy. Nonetheless, it has continued to evolve into an exciting area of active work. With the advent of endoscopic ultrasound (EUS) based procedures, new vistas have opened up. EUS-guided liver biopsies, portal hypertension management, and multiple new procedures are being described. EUS also plays a large role in the management of patients in the peritransplant period. With this review, we present an overview of the role of EUS in the field of hepatology as well as during the peritransplant period and its applications.